Time efficient method for defocus error compensation in tomographic phase microscopy - Kostencka, Julianna; Kozacki, Tomasz; Dudek, Michał; Kujawińska, Małgorzata (Photonics Letters of Poland, 2014)
We present a holographic method for defocus error compensation in tomographic phase microscopy, which enables high quality reconstruction in the presence of a meaningful run-out error of the measurement system. The proposed method involves indirect determination of the sample displacement from the in-focus plane. The sought quantity is deduced from the transverse movement of the rotating sample, which can be determined with high precision using correlation-based techniques. The proposed solution features improved accuracy and reduced computation time compared to the conventional autofocusing-based approach. The validity of the concept is experimentally demonstrated by tomographic reconstruction of an optical microtip. Full Text: PDF References S. Kou, C. Sheppard, "Image formation in holographic tomography", Opt. Lett. 33, 2362 (2008). CrossRef A. C. Kak and M. Slaney, Principles of Computerized Tomographic Imaging (New York, SIAM 2001). CrossRef T. C. Wedberg, J. J. Stamnes, and W. Singer, "Comparison of the filtered backpropagation and the filtered backprojection algorithms for quantitative tomography", Appl. Opt. 34, 6575 (1995). CrossRef J. Kostencka and T. Kozacki, "Optical diffraction tomography: accuracy of an off-axis reconstruction", Proc. SPIE 9132, 91320M (2014) CrossRef A. Kuś et al., "Tomographic phase microscopy of living three-dimensional cell cultures", J. Biomed. Opt. 19, 46009 (2014) CrossRef J. Kostencka, T. Kozacki, M. Dudek, and M. Kujawińska, "Noise suppressed optical diffraction tomography with autofocus correction", Opt. Express 22, 5731 (2014) CrossRef W. Górski, "Tomographic imaging of photonic crystal fibers", Opt. Eng. 45, 125002 (2006) CrossRef F. Charrière et. al., "Cell refractive index tomography by digital holographic microscopy", Opt. Lett. 31, 178 (2006) CrossRef Y. Jeon and C. K. Hong, "Rotation error correction by numerical focus adjustment in tomographic phase microscopy", Opt. Eng. 48, 105801 (2009) CrossRef P. Langehanenberg, B. Kemper, D. Dirksen, and G. von Bally, "Autofocusing in digital holographic phase contrast microscopy on pure phase objects for live cell imaging", Appl. Opt. 47, D176 (2008) CrossRef J. Kostencka, T. Kozacki, and K. Liżewski, "Autofocusing method for tilted image plane detection in digital holographic microscopy", Opt. Commun. 297, 20 (2013) CrossRef K. Liżewski, S. Tomczewski, T. Kozacki, and J. Kostencka, "High-precision topography measurement through accurate in-focus plane detection with hybrid digital holographic microscope and white light interferometer module", Appl. Optics 53, 2446 (2014) CrossRef T. Kozacki, M. Józwik, and R. Józwicki, "Determination of optical field generated by a microlens using digital holographic method", Opto-Electron. Rev. 17, 58 (2009) CrossRef I. Yamaguchi and T. Zhang, "Phase-shifting digital holography", Opt. Lett. 22, 1268 (1997) CrossRef M. Kujawińska et al., "Interferometric and tomographic investigations of polymer microtips fabricated at the extremity of optical fibers", Proc. SPIE 8494, 849404 (2012) CrossRef T. Kozacki, K. Falaggis, and M. Kujawińska, "Computation of diffracted fields for the case of high numerical aperture using the angular spectrum method", Appl. Opt. 51, 7080 (2012) CrossRef